ANALISIS DETERMINAN KEJADIAN STUNTING PADA BALITA - Yespy Anna Wahyu (Jurnal Kesehatan Madani Medika (JKMM), 2019)
INTRODUCTION the problem of nutrition the impact on human resources is still going on in Indonesia. The number of children who experience stunting as much as 27.5% in 2016. This means that 1 in 3 children are experiencing a stunting. The purpose of this research is to analyze the factors giving of nutrition, LOW BIRTH WEIGHT, fetal growth and income against Gen. stunting on toddlers. RESEARCH METHODOLOGY the study was observational, analytic. Variables include low birth weight, the height of the fundus uteri, gift of nutrition and income. The sample is selected by sampling a number of exposure fix 150 with comparison 1:2. Data collection using keusioner, and medical record (KIA). The RESULTS there are influences of nutrition (b = 2.54; CI = 1.63 up 3.44; p = 0.001), LBW < (b =-2.10; CI = 1.33-to-2.87; p = 0.001), growth < fetal (b = 5.95; CI = 3.88 to 8.03; p = 0.001) and income < against Gen. stunting in toddlers (b =-1.38; CI = 2.28 to-0.48; p = 0.003). DISCUSSION of the causes of the incidence of stunting in toddlers is a complex thing. The incidence of stunting begins from malnutrition during pregnancy and diperberat with malnutrition in the first five years the growth of toddlers. CONCLUSION there is influence the granting of nutrition, LOW BIRTH WEIGHT, fetal growth and income against Gen. stunting on toddlers.